ASSOCIATION BETWEEN SMOKING WITH MIGRAINE ATTACKS FREQUENCY AND PAIN INTENSITY IN CHRONIC MIGRAINE PATIENTS - Fitria Adinda S, Rusli Dhanu & Fasihah Irfani Fitri (International Journal of Research Science and Management, 2019)
Background: Smoking is a risk factor for chronic pain. Smoker patients with chronic pain also have more severe pain intensity. The relationship between migraines and smoking is still controversial. This study aims to determine the relationship of smoking to the frequency of attacks and pain intensity in chronic migraine patients. Method: This study used a cross-sectional design, in chronic migraine outpatient in Adam Malik General Hospital Medan, Indonesia. The diagnosis is based on anamnesis according to the Classification of International Headache Society 2nd Edition. Migraine attack frequency and smoking habits are obtained from research data collection sheets. Pain intensity was assessed by visual analog scale (VAS). Results: Of all 33 patients, there was 14 men (42.4%) and 19 women (57.6%). The number of smoker were 12 patients (36.4%). The mean frequency of attacks was 3.03 ± 2.01 with the highest frequency was moderate attacks (60.6%). The mean VAS was 6.85 ± 1.81, with the highest pain intensity found in severe pain intensity (51.5%). With Fisher's test, it was found that there was a significant relationship between smoking and the frequency of attacks (p = 0.001) and the Chi Square Test had a significant relationship between smoking and pain intensity (p = 0.005). Conclusion: There is a significant relationship between smoking with the migraine attack frequency and pain intensity in chronic migraine patients.